The α and β diversities in the fish assemblages of the promiss̃ao reservoir (SP-Brazil): Scales, complexities and ecotone heterogeneity - Do Amaral, B. D. [UNESP]; Petrere M., Jr [UNESP] (My University, 2001)
This paper characterizes the fish assemblage and its interaction with different ecotones within the reservoir. The transformation of a river basin into a cascade of reservoirs produces new ecotones which interact differentially with the spatial\temporal distribution of fish species, their diversity, trophic structures, etc. So the variations of the fish fauna are described to understand better the practices of conservation and management of these reservoirs. The concepts of α and β diversities are related to the concepts of scale, complexity and heterogeneity. Scale comprises the longitudinal, horizontal and vertical variation which are represented by the complexity and heterogeneity of the fish assemblage in the reservoir. Complexity exhibits the variations in ecological data interpretation according to environmental variability or type of data. Heterogeneity describes the variations in species assemblages related to different ecotones. The sampled ecotones were: forest, agricultural land, beaches and mouths of tributaries, each with three replications. Cluster analysis of the environmental factors revealed two distinct ecotonal groups: i) forest, agricultural land and beach; and ii) the tributary mouths. The ANOVAS indicated two possible patterns of diversity: 1 - heterogeneity within the fish assemblage represented by number of species, and differences between the ecotones; 2 - homogeneity within the fish assemblage described by the biomass of different species. The β diversities were congruent with environmental factors giving evidence of the horizontal scale within the reservoir. The forest ecotones revealed higher heterogeneity in the coexistence of fish species than did the with other ecotones. This fact is explained by the littoral areas close to the forest fragments with more refuge, increasing the environmental structural diversity. So it reinforces the importance of the forest as refuge enhancing fish dispersal. The fish assemblages related to agricultural land and beaches were more similar. Agricultural land and pasture ware the dominant ecotone on the reservoir margins.
Keywords: Assemblage; Diversity; Ecotones and heterogeneity; Fish; Reservoir